Surgical Management of Advanced and Metastatic Renal Cell Carcinoma: A Multidisciplinary Approach - Shinder, Brian M.; Rhee, Kevin; Farrell, Douglas; Farber, Nicholas J.; Stein, Mark N.; Jang, Thomas L.; Singer, Eric A. (Frontiers in Oncology, 2017)
The past decade has seen a rapid proliferation in the number and types of systemic therapies available for renal cell carcinoma. However, surgery remains an integral component of the therapeutic armamentarium for advanced and metastatic kidney cancer. Cytoreductive surgery followed by adjuvant cytokine-based immunotherapy (predominantly high dose interleukin 2) has largely given way to systemic targeted therapies. Metastasectomy also has a role in carefully selected patients. Additionally, neoadjuvant systemic therapy may increase the feasibility of resecting the primary tumor, which may be beneficial for patients with locally advanced or metastatic disease. Several prospective trials examining the role of adjuvant therapy are underway. Lastly, the first immune checkpoint inhibitor was approved for metastatic renal cell carcinoma in 2015, providing a new treatment mechanism and new opportunities for combining systemic therapy with surgery. This review discusses current and historical literature regarding the surgical management of patients with advanced and metastatic renal cell carcinoma and explores approaches for optimizing patient selection.